2021
DOI: 10.1016/j.clnesp.2021.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Changes in energy drink consumption during the COVID-19 quarantine

Abstract: The present letter to editor comments the manuscript "Caliskan SG, Kilic MA, Bilgin MD. Acute effects of energy drink on hemodynamic and electrophysiologic parameters in habitual and non-habitual caffeine consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…As caffeine might be the most consumed psycho-stimulant around the world, and due to its likely complex effect on anxiety, further research in this field is needed. Moreover, results from recent studies suggested an increase in coffee, tea, and energy drink consumption during the COVID-19 pandemic [ 18 , 19 , 20 ]; as these beverages are the principal caffeine sources, caffeine intake might have also increased, and have become an additional risk factor for anxiety during this period and possibly beyond. The reported increased anxiety disorder prevalence during the COVID-19 pandemic in 2020–2021 underscores the urgency to strengthen mental illness prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As caffeine might be the most consumed psycho-stimulant around the world, and due to its likely complex effect on anxiety, further research in this field is needed. Moreover, results from recent studies suggested an increase in coffee, tea, and energy drink consumption during the COVID-19 pandemic [ 18 , 19 , 20 ]; as these beverages are the principal caffeine sources, caffeine intake might have also increased, and have become an additional risk factor for anxiety during this period and possibly beyond. The reported increased anxiety disorder prevalence during the COVID-19 pandemic in 2020–2021 underscores the urgency to strengthen mental illness prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the isolation measures related to the pandemic had notable consequences on people's wellbeing and behaviors [45,46], it is possible that even EDs consumption changed in the population examined during that emergency situation. In fact, there is some evidence that students increase EDs use during quarantine periods as a way to cope with stress and boredom [47]. However, our study was not aimed at detecting changes that occurred in ED consumption habits during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…During the recent quarantine induced by the spread of COVID-19, changes in drinking habits have been reported that have also affected young subjects [ 6 ]. We recently analyzed on a group of Italian students´ changes in ED´s consumption habits occurred during the social quarantine for COVID-19.…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 99%